Isolation enhancement of metamaterial structure MIMO antenna for WiMAX/WLAN/ITU band applications - Suneetha, Pasumarthi; Naik, Kethavathu Srinivasa; Muthusamy, Pachiyannan (International journal of microwave and wireless technologies, 2022)
The μ-negative metamaterial (MNG) two-element MIMO antenna design was proposed in this article for WiMAX (2.5–2.8 GHz), WLAN (3.2–5.9 GHz), and ITU band (8.15−8.25 GHz) applications. The first design of the MIMO antenna operates at 2.7 and 4.9 GHz frequencies. In order to reduce the mutual coupling, a defective ground structure is used. For further isolation improvement, an MNG unit cell is placed in between the two radiating elements at a distance of 10 mm. The designed antenna elements have better than −23 dB coupling isolation between the two radiating elements. Moreover, with MNG an additional frequency of 8.2 GHz is obtained, which is useful for ITU band applications. The proposed antenna bandwidth is expanded by 19% in the lower operational band, 20% in the second operational band, and 32% in the higher frequency band with the MNG unit cell. From the analysis, the proposed antenna is suitable for WiMAX/WLAN/ITU band applications because of its low enveloped correlation coefficient, and highest directive gain and low mutual coupling between the radiating components. The proposed antenna was simulated, fabricated, and measured with the help of the Schwarz ZVL vector network analyzer and anechoic chamber. Both measured and simulated results are highly accurate and highly recommended for WiMAX/WLAN/ITU bands.